Problematika Keterwakilan Perempuan dalam pengisian keanggotaan Panitia Pemilihan Kecamatan di Kabupaten Musi Rawas Utara - ARIS WIDODO; Robi Cahyadi Kurniawan; Tabah Maryanah (Universitas Indo Global Mandiri, 2023)
ABSTRACT The domination of men in the membership of the District Election Commitee in the 2024 Election in North Musi Rawas Regency is still a problematic note of women’s representation in filling in the membership of the District Election Commitee. This study answers the problem of not having any female repsentatives to fill the membership positions of the District Election Commitee for the 2024 Elections in North Musi Rawas Regency. The method used in this research is descriptive qualitative method through interviews and documentation. The results of the study show that the 30 % quota for women’s repsentation in filling in the membership of the District Election Commitee in the 2024 election in North Musi Rawas Regency is due to the fact that women’s participation has not been maximized in registering for the selection test for prospective PPK members, furthemore, the capacities and capabilities of women have not been sufficient as members of the District Election Commitee which were concluded from the test results of the interviews. As for efforts to overcome the problem of women’s representation in filling out PPK membership in elections, namely the need for support from election organizers to involve women more as members of the voting Commitee, Voting Organizing Group, Voter Data Updating Officers as well as Election observers, the next effort is to strengthen political education for women through outreach, workshops and other activities in the community so that wonen have the confidence to be able ro compete with men in the selection of members of the adhoc election management body. Keywords : Problem, women’s representation, District Election Commitee member ABSTRAK Dominasi laki – laki dalam keanggotaan Panitia Pemilihan Kecamatan pada Pemilu Tahun 2024 di Kabupaten Musi Rawas Utara masih menjadi catatan problematika keterwakilan perempuan dalam pengisian keanggotaan Panitia Pemilihan Kecamatan tersebut. Kajian ini menjawab permasalahan tidak adanya perwakilan perempuan satupun yang mengisi kedudukan keanggotaan Panitia Pemilihan Kecamatan Pemilu Tahun 2024 di Kabupaten Musi Rawas Utara. Metode yang digunakan dalam penelitian ini adalah metode kualitatif diskriptif melalui wawancara dan dokumentasi. Adapun hasil kajian menunjukkan bahwa tidak terpenuhinya kuota 30 % keterwakilan perempuan dalam pengisian keanggotaan Panitia Pemilihan Kecamatan pada penyelenggaraan Pemilu Tahun 2024 di Kabupaten Musi Rawas Utara disebabkan belum maksimalnya partisipasi perempuan dalam mendaftarkan diri untuk tes seleksi calon anggota PPK selanjutnya kapasitas dan Kapabilitas perempuan belum memadai sebagai anggota Panitia Pemilihan Kecamatan yang disimpulkan dari test hasil wawancara. Adapun upaya mengatasi permasalahan keterwakilan perempuan dalam pengisian keanggotaan PPK pada Pemilu yaitu diperlukan dukungan dari penyelenggara Pemilu untuk lebih melibatkan perempuan sebagai anggota Panitia Pemungutan Suara, Kelompok Penyelenggara Pemungutan Suara, Petugas Pemutakhiran data pemilih maupun sebagai pemantau Pemilu, upaya berikutnya yaitu penguatan pendidikan politik terhadap perempuan melalui sosialisasi, workhshop dan kegiatan – kegiatan lainnya di dalam masyarakat sehingga perempuan memiliki kepercayaan diri untuk dapat berkompetisi dengan laki – laki pada seleksi anggota badan adhoc penyelenggara Pemilu. Kata kunci : Problematika, keterwakilan perempuan. anggota Panitia Pemilihan Kecamatan